Interactive Learning Media to Improve Learning Outcomes in Pancasila Education Among Elementary School Students - Kamarudin; Manan; Akbar, Azaz; Irwan; Sari, Eka Rosmitha; Wotu, Asma H.J (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2025)
Study was motivated by the gap between conventional teaching approaches and the needs of elementary school students in understanding Pancasila values in a contextual and meaningful way. Many instructional practices remain teacher-centered, lacking the capacity to engage students actively and stimulate their interest. The purpose of this research is to examine the effectiveness of interactive learning media in improving student learning outcomes in the subject of Pancasila Education. This study employed a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The research subjects were fifth-grade students at Public Elementary School Number 1 Kaobula, divided into an experimental group and a control group. The research instrument consisted of learning outcome tests administered before and after the intervention. Results revealed that students who learned using interactive learning media demonstrated significantly higher achievement compared to those who received conventional instruction. This difference was further supported by t-test analysis and effect size calculations, which indicated a strong and meaningful impact. Conclusion of this study is that interactive learning media is effective in enhancing students’ understanding of Pancasila values and provides a more engaging, active, and meaningful learning experience within the context of character education at the elementary school level.